Pannexin‐1 mediated ATP release in adipocytes is sensitive to glucose and insulin and modulates lipolysis and macrophage migration. (14th October 2019) - Tozzi, Marco; Hansen, Jacob B.; Novak, Ivana
Abstract: Aim: Extracellular ATP signalling is involved in many physiological and pathophysiological processes in several tissues, including adipose tissue. Adipocytes have crucial functions in lipid and glucose metabolism and they express purinergic receptors. However, the sources of extracellular ATP in adipose tissue are not well characterized. In the present study, we investigated the mechanism and regulation of ATP release in white adipocytes, and evaluated the role of extracellular ATP as potential autocrine and paracrine signal. Methods: Online ATP release was monitored in C3H10T1/2 cells and freshly isolated murine adipocytes. The ATP release mechanism and its regulation were tested in cells exposed to adrenergic agonists, insulin, glucose load and pharmacological inhibitors. Cell metabolism was monitored using Seahorse respirometry and expression analysis of pannexin‐1 was performed on pre‐ and mature adipocytes. The ATP signalling was evaluated in live cell imaging (Ca 2+, pore formation), glycerol release and its effect on macrophages was tested in co‐culture and migration assays. Results: Here, we show that upon adrenergic stimulation white murine adipocytes release ATP through the pannexin‐1 pore that is regulated by a cAMP‐PKA–dependent pathway. The ATP release correlates with increased cell metabolism and is sensitive to glucose. Extracellular ATP induces Ca 2+ signalling and lipolysis in adipocytes and promotes macrophage migration. Importantly, ATP release is markedly inhibited by insulin, which operates via the activation of phosphodiesterase 3. Conclusions: Our findings reveal an insulin‐pannexin‐1‐purinergic signalling crosstalk in adipose tissue and we propose that deregulation of this signalling may contribute to adipose tissue inflammation and type 2 diabetes.